2019
DOI: 10.3389/fchem.2019.00550
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Large Non-equilibrium Tunnel Magnetoresistance Ratio in CoRhMnGe Based Magnetic Tunnel Junction by Interface Modification

Abstract: Equiatomic quaternary Heusler compounds (EQHCs) generally have the advantages of high Curie temperature, large spin polarization and long spin diffusion length, and they are regarded as one of the most promising candidates for spintronics devices. Herein, we report a theoretical investigation on an EQHC CoRhMnGe based magnetic tunnel junction (MTJ) with (i) MnGe-terminated interface and (ii) modified pure Mn terminated interface, i.e., MnMn-terminated interface. By employing first principle calculations combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…An MTJ fabricated using a heterostructure having enhanced interfacial magnetization was reported, exhibiting an enhancement in TMR value from 50% to 170%. 146,147 A higher TMR value was also reported by theoretical calculation on the heterojunction of CoRhMnGe/MgO/CoRhMnGe, 143 which revealed that the modification of interface termination from Mn-Ge to Mn-Mn in the heterojunction led to a higher TMR value of the order of 10 5 % and strong spin filter ability (as shown in Fig. 10b and c).…”
Section: Enhancing the Performance Of Magnetic Tunnel Junctionsupporting
confidence: 57%
See 2 more Smart Citations
“…An MTJ fabricated using a heterostructure having enhanced interfacial magnetization was reported, exhibiting an enhancement in TMR value from 50% to 170%. 146,147 A higher TMR value was also reported by theoretical calculation on the heterojunction of CoRhMnGe/MgO/CoRhMnGe, 143 which revealed that the modification of interface termination from Mn-Ge to Mn-Mn in the heterojunction led to a higher TMR value of the order of 10 5 % and strong spin filter ability (as shown in Fig. 10b and c).…”
Section: Enhancing the Performance Of Magnetic Tunnel Junctionsupporting
confidence: 57%
“…10b and c). 143 Moreover, the higher TMR of MTJ containing a modified interface was sustained at bias voltage, whereas this was not observed in the unmodified interface in the MTJ. This shows the advantageous possibility of interface modification in achieving robust TMR for MTJ independent of external perturbation.…”
Section: Applications Based On Interfacial Magnetismmentioning
confidence: 98%
See 1 more Smart Citation